2011
DOI: 10.1007/s11618-011-0189-0
|View full text |Cite
|
Sign up to set email alerts
|

16 Vocational education and training and transitions into the labor market

Abstract: Stage 6 of the German National Educational Panel Study is devoted to youth's transitions from school into the labor market. In all Western societies, vocational education and training (VET) systems face a number of challenges, including the need to adapt to increasing skill requirements across the economy and handle the danger of producing an "underclass" of low-skilled youth. This chapter presents the life-course approach for investigating school-leavers' pathways from school into the labor market within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Firstly, they shift the educational content more closely toward the actual competencies needed in the workplace (Ludwig-Mayerhofer et al 2011;Mayer and Solga 2008). For example, labelling the following themes "Ausbildung 4.0" (by which, in imitation of "Industry 4.0, " we mean "VET 4.0"; Frey and Osborne 2013), Zinn (2015) picked out digitization, industrial automation, and interconnectedness as central themes for a future reorganization of learning processes in VET.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, they shift the educational content more closely toward the actual competencies needed in the workplace (Ludwig-Mayerhofer et al 2011;Mayer and Solga 2008). For example, labelling the following themes "Ausbildung 4.0" (by which, in imitation of "Industry 4.0, " we mean "VET 4.0"; Frey and Osborne 2013), Zinn (2015) picked out digitization, industrial automation, and interconnectedness as central themes for a future reorganization of learning processes in VET.…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring successful transition enables better retention and engagement with study as learners are making informed choices (DfES, 2007;WG, 2018a). As other studies have shown, continued schooling and vocational and professional training remain of primary importance for a skilled work force, careers and social integration (The Northern Powerhouse Partnership 2018;Maurice-Takerei 2017;Ludwig-Mayerhofer et al 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The German education system is characterized by a distinction between academic general education on the one hand, and practical vocational training on the other hand (Ludwig-Mayerhofer et al 2011). Also characteristic is the so- (Daniel et al 2019).…”
mentioning
confidence: 99%
“…Also characteristic is the so- (Daniel et al 2019). It is quite common for health-related occupations like medical assistants and nurses, as well as for Kindergarten teachers and social workers (Ludwig-Mayerhofer et al 2011). Graduates from VET receive occupation-specific certificates, which are required in order to work as skilled labor in Germany (e.g., Bol et al 2019;Graf 2015;Hillmert et al 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation